Is parasitic behavioural manipulation endangered as a hypothesis? - Phua, Samantha Jo Su-Ying (2012)
Host behavioural manipulation is a phenomenon that occurs in various host-parasite systems, and has been widely studied. Many have argued that manipulation is costly to a parasite and there would be selection pressures against its prevalence. In the examples of conflicting manipulative parasites, hitch-hikers and conspecifics that establish in different host organs, this review explores the various costs that manipulative parasites incur, showing that manipulation of a host is indeed costly. However, there are also ways in which parasites are able to lower these costs, shown in the example of ‘love-potion’ parasites, or by forming commensal relationships with the hosts. Overall, manipulation would prevail in a parasite population for as long as manipulation is beneficial to the parasite, the benefits being better transmission to a definitive host and the eventual improved fecundity and survival.